2007
DOI: 10.1016/j.conbuildmat.2006.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Flexural responses of hybrid steel–polyethylene fiber reinforced cement composites containing high volume fly ash

Abstract: Strain hardening and multiple cracking behavior of hybrid fiber reinforced cement composites containing different hybrid combinations of steel and polyethylene (PE) fibers under four-point bending are reported. The total volume fraction of fibers was kept constant at 2.5% to maintain a workable mix. Effects of increase in fly ash content as partial replacement of cement beyond 50%, such as 60% and 70% on the flexural response of hybrid steel-PVA (Polyvinyl Alcohol) and steel-PE fiber composites are also evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(71 citation statements)
references
References 11 publications
3
66
0
2
Order By: Relevance
“…Therefore, by reinforcing geopolymer matrix with PE fibre both high strength and high ductility can be achieved simultaneously. A number of research is reported on the ductility of PE fibre reinforced cement based composites [4][5]. However, no research so far is reported on geopolymer composite containing PE fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by reinforcing geopolymer matrix with PE fibre both high strength and high ductility can be achieved simultaneously. A number of research is reported on the ductility of PE fibre reinforced cement based composites [4][5]. However, no research so far is reported on geopolymer composite containing PE fibres.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the obvious advantages of the HFRC composites in construction practices are improved homogeneity, better crack management, possibility of slender structural members (Almusallam et al, 2013(Almusallam et al, , 2014Yu et al, 2014;Markovic et al, 2006). However, to ensure a balance between ultimate strength and strain capacity, optimum volume/weight proportion of different fibers is desired (Ahmed et al, 2007). For static loading conditions, HFRC composites result in better energy absorbing properties compared with that of mono-fiber concrete composites (Chen et al, 1996;Abou El-Mal et al, 2015;Li, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It becomes more popular in these recent years and expected to provide better physical and mechanical properties in concrete for structural purposes. The use of different types of fiber in a suitable combination may potentially improve the mechanical properties of concrete and result in synergic performance [6][7][8][9]. Addition of steel fiber generally provides contribution to the energy absorbing mechanism (bridging action), while nonmetallic fibers offer its ability to delay the formation of microcracks and avoid catastrophic breaking, and also has much lower density [9].…”
Section: Background Lightweight Concrete (Lwc) Applicationmentioning
confidence: 99%